Case report: A community case study of the human-animal bond in animal-assisted therapy: the experiences of psychiatric prisoners with therapy dogs - Smith, Sonia; Dell, Colleen Anne; Claypool, Tim; Chalmers, Darlene; Khalid, Aliya (Frontiers in Psychiatry, 2023)
Prisoners frequently experience chronic loneliness and lack social support, which can exacerbate their struggles with incarceration. According to attachment theory, individuals who are insecurely attached may be more likely to develop unstable relationships and engage in antisocial behavior as adults. In 2015 an animal-assisted therapy (AAT) program was implemented in a Canadian forensic psychiatric facility/prison, a “hybrid” facility that adheres to federal legislation regarding correctional services but follows provincial mental health legislation. The program centers on the development of a human-animal bond (HAB), which serves as a connection between the animals and prisoners. The HAB also addresses issues related to toxic masculinity, which are often present among men incarcerated in correctional facilities, including psychiatric prisons. An instrumental community case study design involving 6 prisoners at a forensic psychiatric facility/prison over 24 AAT sessions between 2015–2019 was undertaken. Interviews with the prisoners and their mental health clinicians were thematically analyzed to explore how the HAB was experienced as a form of attachment. Four themes emerged: safety, physical touch, reciprocity, and acceptance. These themes suggest that the therapy dogs have the potential to serve as a surrogate attachment figure for prisoners, mitigating their experiences of disconnection and fostering their development of interpersonal connections. This suggests attachment theory underpins the HAB and highlights the contribution of AAT practice and research in forensic psychiatric facilities/prisons. This study also suggests that the program's offering of prosocial support and nurturance/caring aligns with the specific criminogenic risks and needs identified within Correctional Service Canada's Risk-Need-Responsivity (RNR) model for rehabilitation. Continued research and attention should be paid to AAT programs as a valuable addition to the range of support networks available to prisoners in psychiatric or non-psychiatric institutions.